Transcatheter versus surgical closure of atrial septal defect: Comparison of early result and complication - Yayu Dwinita Jasin; Mahrus A. Rahman (Amaltea Medical Publishing House, 2024)
Background. Surgical therapy for closure of atrial septal defect with cardiopulmonary bypass is the gold standard. Transcatheter closure has become an alternative for the treatment of atrial septal defect because 80-90% of atrial septal defects can be resolved without surgery. The success of transcatheter closure of atrial septal defect is almost 80% of all patients with atrial septal defect. Objective. To analyze the differences in the results of transcatheter and surgical closure of atrial septal defects Method. The type of research is observational analytic with a cross-sectional design. The sample is medical record data from pediatric patients with atrial septal defect who underwent transcatheter and surgical closure of the atrial septal defect between January 1, 2019 and June 30, 2023 at "Dr. Soetomo" Surabaya. All subjects with incomplete data will be excluded. Results. The total research subjects were 81 subjects, divided into 2 groups: transcatheter 41/81 (50.6%) and surgical 40/81 (49.6%). Transcatheter and surgical procedures had similar success rates (100% vs 92.5%, p=1.116). Transcatheter procedures had a longer ICU stay (0.07 day vs 3 days, p<0.001) and longer hospital stay (4,8 days vs 7,3 days, p<0.001) than surgical procedures. The total procedure cost of transcatheter procedures was also cheaper than surgical procedures (61 million vs 91 million, p<0.001). Complications of transcatheter procedures were also lower than surgical procedures (12.2% vs 52.5%, p<0.001). Conclusion. Transcatheter closure of atrial septal defects showed excellent result, shorter ICU and hospital stay, lower costs, and fewer complications.